Global and Regional Roles of the Russian Transport Infrastructures - Erdősi, Ferenc (Discussion Papers, 2012)
The world’s largest country in a returning to normal international political environment is practically converting its unique geographical conditions into direct material benefits at an increasing success by playing a land bridge role and building the necessary transport corridors between the Atlantic/Baltic Europe - Easter Asia and also between Northern Europe Caspian Sea region and Persian Gulf area. Making these Trans-Eurasian corridors attractive for international tran¬sit and the maximization of profits gained directly (through rendering services) and indirectly (through the allocation of foreign capital in the corridor zones) is a national interest. The development of infrastructure enabling the trans¬portation of extra heavy goods and commodities is urged both by the demands of foreign trade and by the semi-global scale of transit services offered. In this paper we are going to give an overview on the efforts of ‘continental’ Russia for building a sea gateway having made for several centuries to join to world trade and for the safe manoeuvring of its empire-sized military fleet and to find a modus vivendi compromise for the geographical constraint situation of our time. To what extent will Russia be able to perform the functions of transport con¬nection between Europe and Eastern Asia, the two major economic powers of the world besides the emerging new competitor route alternatives is one of the most exciting world economic questions of our age.